2011
DOI: 10.1038/oby.2011.246
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Associated With Obesity: Relationship With Blood and Bone Marrow Endothelial Cells

Abstract: The purpose of this study was to assess the inflammatory nature of obesity and its effect on blood and bone marrow endothelial cell populations. Obese patients (BMI ≥30) had significantly higher concentrations of the inflammatory marker C‐reactive protein (CRP) (P = 0.03) and lower concentrations of the anti‐inflammatory cytokine interleukin‐10 (IL‐10) (P = 0.05). This cytokine profile is consistent with obesity being an inflammatory condition and is further supported by the significant correlation between tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Obesity may contribute to low-grade inflammation. It has been found that pro-inflammatory cytokines such as IL-6 and adiponectin are released by adipose tissue (43,44). However, the linkage between body fat accumulation and inflammation needs to be investigated in more detail in future.…”
Section: Discussionmentioning
confidence: 98%
“…Obesity may contribute to low-grade inflammation. It has been found that pro-inflammatory cytokines such as IL-6 and adiponectin are released by adipose tissue (43,44). However, the linkage between body fat accumulation and inflammation needs to be investigated in more detail in future.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, altered cell functions have also been reported in obese individuals. For example, reduced numbers of endothelial cell have been observed in the bone marrow of obese patients 7 . Wang et al also found that contribution of bone marrow cells for tissue homeostasis was affected by diabetes and obesity 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Stromal cells residing in the marrow spaces give rise to cellular populations of the marrow micro-environment, such as osteoblasts and adipocytes. It is postulated that chemotherapy might induce a switch in the bone marrow stromal cells towards adipogenic differentiation at the expense of haemopoiesis (19). At the morphometric level, the highest area of fat in bone marrow sections was recorded in gIIa, representing a significant increase compared to all other groups and subgroups.…”
Section: Discussionmentioning
confidence: 99%